Mortality trends in external causes of death in people with mental health disorders in Sweden, 1987–2010. Issue 2 (March 2019) - Hällgren, Jonas; Ösby, Urban; Westman, Jeanette; Gissler, Mika
Aim: We investigated mortality from external causes in Swedish people who had been hospitalised with a severe mental disorder. Methods: Hospitalisations in people aged 15 years or older admitted to hospital with a main diagnosis of schizophrenia, bipolar mood disorder or unipolar mood disorder between 1987 and 2010 were linked to their causes of death. Results: The mortality rate from all external causes was 20-fold higher in those with unipolar mood disorder, 15-fold higher in those with bipolar disorder and 12-fold higher in those with schizophrenia than in the general population. Over the study periods, the mortality rate declined more for people with unipolar mood disorder (−35%) and schizophrenia (−29%) than the total population (−25%) and those with bipolar mood disorder (−15%). The suicide rate declined most for those with unipolar mood disorder and schizophrenia (−42% for both) and less for the general population (−37%) and those with bipolar mood disorder (−21%). For external causes other than suicide, the mortality rate declined in the general population (−17%) but increased in people with schizophrenia (14%), bipolar mood disorder (30%) and unipolar mood disorder (52%). Conclusions: People with mental disorders have high but declining excess mortality from suicide. Mortality from other external causes has increased, as has the gap in mortality rates between psychiatric patients and the general population.